Labeling of Erythrocytes by Porphyrin‐Phospholipid. Issue 1 (29th October 2020) - Kumar, Sunanda; Jiang, Dawei; Sun, Boyang; Seeley, Kaelyn V.; Engle, Jonathan W.; Sia, Zachary; He, Xuedan; Neelamegham, Sriram; Cai, Weibo; Lovell, Jonathan F.
Abstract : A method is developed for membrane labeling of erythrocytes with porphyrin‐phospholipid (PoP). To generate a concentrated PoP solution for labeling human red blood cells (RBCs), various surfactants and solvents are screened to identify conditions that avoid hemolysis while minimizing nonspecific PoP coprecipitation with RBCs in the pellet during centrifugation washes. Cholate, Tween 80, and Tween 40 are identified as useful surfactants for this purpose. When labeled RBCs are mixed with unlabeled ones, substantial nonspecific PoP exchange is observed. Egg‐yolk lecithin is included in a washing buffer to remove loosely bound PoP and reduce PoP exchange with unlabeled erythrocytes, based on flow cytometry and photodynamic hemolysis assays. Murine RBCs that are labeled with 64 Cu‐chelated PoP display altered biodistribution with longer blood circulation relative to directly administered 64 Cu‐chelated PoP. Abstract : A method is developed to label red blood cells with porphyrin‐phospholipid (PoP). PoP is first dissolved in surfactant micelles during for labeling, and then red blood cells are washed with lecithin. 64 Cu‐PoP‐labeled red blood cells have longer circulation time compared with 64 Cu‐PoP alone and are used for biodistribution analysis and mouse imaging.